Tuberculosis of the Central Nervous System : Pathogenesis, Imaging, and Management - Turgut, Mehmet; Akhaddar, Ali; Turgut, Ahmet T.; Garg, Ravindra K. (Springer International Publishing : Imprint: Springer, 2017)
Written and edited by leading international authorities in the field, this book provides an in-depth review of knowledge of tuberculosis of the central nervous system, with emphasis on clinical, diagnostics, and therapeutic features. Tuberculosis, one of the most lethal diseases in human history, still poses a serious threat in the world together with economic and social problems, although a great progress in the fight against this infectious disease in the last century. It covers the full range of tuberculosis of central nervous system and the chapters are organized into six sections: (1) the cranial; (2) the spinal; and (3) the peripheral portions of the nervous system; followed by (4) a section on the laboratory studies in tuberculosis; (5) a section on medical and surgical therapy; and (6) further insights into tuberculosis. This comprehensive reference book will be an ideal source for neurosurgeons, neurologists and specialists upon infectious diseases seeking both basic and more sophisticated information and surgical procedures relating to the complications associated with tuberculosis involving the spine, brain and peripheral nerves.
Keywords: Medicine.; Infectious diseases.; Neurology.; Neurosurgery.; elektronické knihy; electronic books